Very Early Diagnosis and Management of Congenital Erythropoietic Porphyria. (June 2023) - Desjardins, Marie-Pier; Naccache, Lamia; Hébert, Audrey; Auger, Isabelle; Teira, Pierre; Pelland-Marcotte, Marie-Claude
Congenital erythropoietic porphyria (CEP), a rare form of porphyria, is caused by a defect in the heme biosynthesis pathway of the enzyme uroporphyrinogen III synthase (UROS). Uroporphyrinogen III synthase deficiency leads to an accumulation of nonphysiological porphyrins in bone marrow, red blood cells, skin, bones, teeth, and spleen. Consequently, the exposure to sunlight causes severe photosensitivity, long-term intravascular hemolysis, and eventually, irreversible mutilating deformities. Several supportive therapies such as strict sun avoidance, physical sunblocks, red blood cells transfusions, hydroxyurea, and splenectomy are commonly used in the management of CEP. Currently, the only available curative treatment of CEP is hematopoietic stem cell transplantation (HSCT). In this article, we present a young girl in which precocious genetic testing enabled early diagnosis and allowed curative treatment with HSCT for CEP at the age of 3 months of age, that is, the youngest reported case thus far.